2015
DOI: 10.4103/0970-0218.164406
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of abuse among community dwelling elderly of Guwahati City, Assam

Abstract: Background:In spite of tremendous impact on health, elder abuse is still an underreported and unrecognized issue.Objectives:To assess the prevalence of abuse among community dwelling elderly and to identify the various risk factors.Materials and Methods:This community-based cross-sectional study was conducted in 10 randomly selected wards of Guwahati city. A total of 331 elderly (60 years and above) were interviewed. Abuse was screened by Hwalek-Sengstock Elder Abuse Screening Test (H-S EAST).Results:The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
58
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 6 publications
9
58
2
1
Order By: Relevance
“…[10][11][12] Our study found that the main perpetrator of abuse was son followed by daughter in laws similar findings were seen in other studies. 6,13 It could be due to most common living arrangement of elders in India where they usually live with their son.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Our study found that the main perpetrator of abuse was son followed by daughter in laws similar findings were seen in other studies. 6,13 It could be due to most common living arrangement of elders in India where they usually live with their son.…”
Section: Discussionmentioning
confidence: 99%
“…reported relatively lower proportion of elderly abuse (9.31%) in Guwahati City, Assam. 2 Such difference of observations might be explained by different study setting and application of different assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study in Guwahati City, Assam reported that more common abuse were neglect and verbal abuse. 2 The study in the seven demographically oldest states in India reported that verbal abuse was mostly encountered followed by disrespect, economic, physical and neglect. 3 The above variation in observations may reflect real variation across different cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations